2015
DOI: 10.1007/s12155-015-9589-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy Crops and Natural Enemies: Host Plant-Mediated Effects of Miscanthus on the Aphid Parasitoid Lysiphlebus testaceipes

Abstract: Miscanthus spp. are biofuel crops that are triggering growing interest worldwide due to their numerous agronomic advantages. Though breeding programs take into account usual key plant traits of agronomic interest (e.g., biomass production, adaptation to broader climatic range), they generally overlook plant attributes relating to pest and pathogen resistance and even more those that may favor or improve the combined use of biological control agents of pests. A recent study showed that the parental species, Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…e ., mated, fed, and without oviposition experience) with a single three-day-old A . fabae nymph in a small Eppendorf tube (0.5 ml), as described in [ 35 ]. Each parasitoid female was only used once.…”
Section: Methodsmentioning
confidence: 99%
“…e ., mated, fed, and without oviposition experience) with a single three-day-old A . fabae nymph in a small Eppendorf tube (0.5 ml), as described in [ 35 ]. Each parasitoid female was only used once.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, some studies using in vitro plants have pointed out that M. sacchariflorus shows a greater resistance to the corn leaf aphid R. maidis than M. sinensis and M . × giganteus . Another study using potted plants has shown that M. sinensis is more resistant than M .…”
Section: Introductionmentioning
confidence: 99%
“…20 Indeed, some studies using in vitro plants have pointed out that M. sacchariflorus shows a greater resistance to the corn leaf aphid R. maidis than M. sinensis and M. × giganteus. 21,22 Another study using potted plants has shown that M. sinensis is more resistant than M. × giganteus, raising the possibility that M. sinensis could represent a better alternative to M. × giganteus under heavy aphid pressure. 20 These studies suggest that Miscanthus breeding programmes should also take into account traits that are related to resistance to insect pests.…”
Section: Introductionmentioning
confidence: 99%